Colour removal from fermentation industry effluents - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1999)
Large amounts of effluents from the fermentation industry are characterized by high COD and colour. Although significant reduction in COD is achieved through biological treatment processes, a substantial amount of colour remains. Coagulation and flocculation with alum acid iron salts are not effective for colour removal. This is due to the nature of colour causing compounds which are almost totally dissolved and resistant to biodegradation. Hence, fermentation industries face difficulties in discharging their coloured effluents into either sewers or surface waters. In this study, colour removal from biological treatment plant effluents of a fermentation industry with lime and ozone was investigated experimentally. Optimum lime dose for reducing the colour to values around 1000 Pt-Co was found as 10.0 g/l, while 0.9 g/l ozone was necessary to obtain the same residual colour. Economic evaluation has indicated that cost of lime treatment was 1.3 to 1.4 USD/m(3) while it was 2.5 USD/m(3) for ozone treatment. Annual total costs for lime and ozone treatment were also estimated as 2 million USD and 3.65 million USD, respectively. (C) 1999 IAWQ Published by Elsevier Science Ltd. All rights reserved.
Keywords: colour; wastewater; treatment; fermentation industry; physico-chemical processes; lime; ozone; PULP